Determinan Pembiayaan Pada Bank Pembiayaan Rakyat Syariah di Indonesia - Husaeni, Uus Ahmad (Faculty of Economic and Business, 2017)
Financing Determinants in The Indonesian Islamic Rural BankIslamic Rural Bank serves as a financial intermediary to carry out the activities of collecting and distributing funds from the public. Therefore, it is necessary to test whether internal factors, which include deposit funds, capital adequacy ratio, financing to deposit ratio and non-performing financing significantly affects to financing. The purpose of this study is to examine the factors that affect the financing in Islamic rural bank in Indonesia. The analytical tool used in this research is multiple linear regression analysis. The results of the study, to simultaneously show that the Third Party Funds, Capital Adequacy Ratio, Financing to Deposit Non-Performing Financing significantly affects to Distribution of Funding in SRB (BPRS), while the rest is explained by other factors not enrolled in this study.DOI: 10.15408/ess.v7i1.4542